Aplikasi Tematis Al-Qur'an Berbasis Web - Wisaksono, Arief; Farihah, Anis; Ariyanti, Novia (Universitas Muhammadiyah Surabaya, 2018)
In the elementary school curriculum know 2013 revision 2017 now the process of teaching and learning is based on themes, namely a teaching and learning process that has teaching materials related to the problem, and local needs that are used as themes or titles in the learning process in study groups. As a leading Islamic school SD Muhammadiyah 8 Tulangan Sidoarjo in every teaching and learning process teachers are required to always associate all teaching material with the Qur'an. The problem is that the support of open tools that can quickly find references to verses of the Qur'an related to a particular theme does not yet exist, so that the teaching and learning process becomes ineffective. To overcome this problem the author provides a program solution. This program will provide solutions that are expected to solve partner problems. The main method used is to use a tool in the form of a web-based thematic application, which is an application that can find references to Ayat Al-Qur'an related to a particular theme. In this application, users simply enter the theme to be discussed, the reference letters and verses and their meanings will appear. With this application, it is expected that teachers can quickly find references to each theme in each teaching material while making time efficiency.